Traditional Uses, Phytochemistry and Biological Activities of Alocasia Species: A Systematic Review - Arbain, Dayar; Sinaga, Lorenskia Maria Regina; Taher, Muhammad; Susanti, Deny; Zakaria, Zainul Amiruddin; Khotib, Junaidi (Frontiers in Pharmacology, 2022)
The genus Alocasia (Schott) G. Don consists of 113 species distributed across Asia, Southeast Asia, and Australia. Alocasia plants grow in tropical and subtropical forests with humid lowlands. Featuring their large green heart-shaped or arrow-shaped ear leaves and occasionally red-orange fruit, they are very popular ornamental plants and are widely used as traditional medicines to treat various diseases such as cancer, jaundice, snake bite, boils, and diabetes. This manuscript reports the ethnopharmacological and phytochemical contents of Alocasia species as well as biological activity of the purified compounds. Research articles were acquired by accessing three scientific databases comprising PubMed, Scopus, and Google Scholar. For this review, specific information was obtained using the general search term “Alocasia” AND “phytochemical” OR “bioactivity” or “pharmacological activity”. The accepted authority of each plant species was referred from www.theplantlist.org. Scientific studies have revealed that the genus is mainly scattered throughout Asia. It has proven clinical and preclinical benefits, which have been associated with various biological properties especially for anticancer and anti-inflammatory. Alocasia species exhibit diverse biological activities that are very useful for medical application, especially alocasgenoside B which was reported to have strong anticancer activity. Among the species, A. cucullate and A. macrorrhiza are the mostly studied with biological activity. Therefore, it is strongly recommended to further explore the relevant use of natural compounds present in the genus Alocasia, particularly as an anticancer agents.